When China Sneezes Does ASEAN Catch a Cold? - Rafiq, Sohrab (IMF Working Papers; Working Paper, 2016)
This paper looks at the effects of a China slowdown on Emerging Market Economies (Indonesia, Malaysia, and Thailand) and Frontier Developing Economies (Cambodia, Lao P.D.R., and Vietnam) in ASEAN. The main finding is that the impact of China growth shocks on ASEAN has risen since the global financial crisis. A one percent decline in China's growth implies a 0.3 percent reduction in growth for ASEAN EMEs and 0.2 for FDEs. An important component of inflation is also shared between ASEAN and China. These magnitudes are double what they were two decades ago due to stronger trade and financial linkages. Finally, a slowdown in China, while having real effects, also has a financial impact via slower credit growth and lower equity prices. This is in line with the existence of both portfolio balance and signaling channels, in which ASEAN market participants absorb news on China economic activity as an indicator over domestic growth prospects.